"I WANTED ONE THING AND GOD WANTED ANOTHER . . . ": The Dilemma of the Prophetic Example and the Qur'anic Injunction on Wife-Beating - Chaudhry, Ayesha S. (The Journal of religious ethics, 2011)
Chapter 4, verse 34 of the Qur'an permits husbands to physically discipline recalcitrant wives. Modern Muslims who find this husbandly privilege discomfiting often rely on Muhammad's prophetic practice to mitigate the meaning of this verse. In light of Muhammad's example of never hitting his own wives, as found in one prophetic report, they reinterpret the verse as restricting and/or voiding a husband's right to physically discipline his wife. This essay provides a critical and expository survey of prophetic reports related to the husbandly privilege to physically discipline wives. The essay argues that the modernists are correct in positing that Muhammad's prophetic practice was to morally censure husbands who hit their wives. However, taken as a whole, it is impossible to ignore that Muhammad's example also unilaterally upheld physical discipline as a husband's marital right.